Pengaruh Latihan Agility dan Perturbation Terhadap Peningkatan Aktivitas Fungsional Pasien Osteoarthritis Lutut Di Posyandu Lansia Pelaihari - Noviyanti, Endah Prasetiya; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2017)
Background: The elderly tend to have decrease in musculoskeletal system. Decrease in musculoskeletal system can affect physical mobility of elderly. One of them is knee pain which is sign of osteoarthritis, have a complaint such as knee pain, joint stiffness in the morning, joint crepitations while active movement and pain of the knee. To reduce pain and improve function in knee Osteoarthritis by giving agility and perturbation exercise. Purpose: To know the effect of agility and perturbation exercise to increase functional activity Osteoarthritis patients Methods: Types of this research is quasi experiment. Research design is One Group Pretest and Posttest With Control Group Design. The first group of elderly given agility and perturbation exercise and second group of elderly were not given exercise. Number of sample research is 40 people with purposive sampling technique which uses criteria of population: inclusion and exclusion. Result: From result of wilcoxon test which obtained from total WOMAC score, there is significant change with score p = 0,000. From result mann whitney test, there is significant differences between average pre test and post test. From these results, that increase of functional activity in treatment group was better than control group. Conclusions: There is effect of agility and perturbation exercise to increase functional activity Osteoarthritis patients. Keywords : Elderly, Knee Osteoarthritis, Agility and Pertubation Exercise